Antifungal Test of Caricature Plant (Graptophyllum pictum [L.] Griff.) Ethanol Extract to The Growth of Candida albicans In Vitro - Victoria Husadani Permata Sari; Sri Haryati; Sigit Setyawan (Nexus Biomedika, 2017)
Introduction: Much of data states that there has been resistance to candidiasis therapy drugs. It is necessary to consider candidiasis therapy using alternative medicines. Caricature plant (Graptophyllum pictum [L.] Griff.) investigated because it suspected contains compounds that have the potential against the growth of Candida albicans, such as alkaloid, saponin, tannin and flavonoid. The purpose of this research is to determine the antifungal effect of caricature plant (Graptophyllum pictum [L.] Griff.) ethanol extract to the growth of Candida albicans in vitro. Methods: This type of research is an laboratory experimental, post test only with control group design. Research conducted at the Laboratory of Parasitology, Faculty of Medicine Sebelas Maret University. The subject of this research is Candida albicans cultured. The measured variable is the caricature plant (Graptophyllum pictum [L.] Griff.) ethanol extract with concentration 15%, 20%, 25%, 30%, 35%, and diameter of inhibition zone. The data were taken after incubation at 37C for 48 hour. Data were analyzed with Pearson correlation test dan one way ANOVA test with Post-Hoc Tamhane test. Results: Pearson correlation test showed that there are positive correlation between the antifungal effect with increase concentration of caricature plant (Graptophyllum pictum [L.] Griff) ethanol extract. There is significant differences between all concentrations with negative control. There is no significant differences between antifungal effects of concentration 35% with ketoconazole. Conclusion: Caricature plant (Graptophyllum pictum [L.] Griff.) ethanol extract starting concentration at 15% has antifungal effect to the growth of Candida albicans. Caricature plant (Graptophyllum pictum [L.] Griff) ethanol extract concentration of 35% is thought to have an equal effect with the antifungal ketoconazole. Keywords: Caricature plant (Graptophyllum pictum [L.] Griff.) ethanol extract, the antifungal effect, Candida albicans